Product Attributes Influencing Rural Consumers'purchase Decision for Micro Packs - An Application of Conjoint Analysis. - Mehra, Preeti (Journal of Rural Development, 2021)
The strategy of micro-packing is an outcome of a tenacious effort being undertaken by companies to create an awareness for their products in the rural market, and to deliver something unique to their customers. However, there lies a need to cognise the proper applicability of this strategy in the rural markets. The specific objective of the study is to analyse the consumer preferences for micro packs with special emphasis on the rural market in India. In order to attain these objectives, a sample of 450 respondents belonging to four cities of Punjab was taken. Non-probability convenient sampling was adopted for selecting the respondents and the data was examined using conjoint analysis. It was found that a calculated and impressive display of micro packs can act as a pull strategy and lure consumers into making an immediate procurement. The manifestation of contents is desirable. A micro pack, that is handy, delightfully displayed and backed up with a celebrity testimonial is contemplated as an ideal product.